Bioactivities of bay leaf (Syzygium polyanthum) fumigant tablets againts Araecerus fasciculatus (De Geer) (Coleoptera: Anthribidae): Bioaktivitas fumigan tablet daun salam (Syzygium polyanthum) terhadap Araecerus fasciculatus (De Geer) (Coleoptera: Anthribidae) - Hasby; Astuti, Ludji Pantja; Rizali, Akhmad (Perhimpunan Entomologi Indonesia, 2024)
The use of bay leaves (Syzygium polyanthum) as an alternative fumigant has the potential to control Araecerus fasciculatus (De Geer (Coleoptera: Antribidae). The objective of this study was to evaluate the bioactivities of bay leaf fumigant tablet (BLFT) with exposure times (24, 48, and 72 h) on adult mortality, oviposition deterrence, inhibition of F1 progeny, and feeding activity of the internal feeder pest, A. fasciculatus. This study was used seven concentration levels of BLFT (i.e., 0, 1.25, 2.5, 3.75, 5, 6.25, and 7.5 ml/l air) replicated four times and arranged in a completely randomized design. The observed variables were adult male and female mortality, number of eggs, F1 progeny, and inhibition of feeding activity. The results showed that bay leaf tablets have very significant potential as a fumigant against A. fasciculatus. Bay leaf tablets fumigant at a concentration of 3.75 ml/l air within 24 hours of application were able 100% inhibit feeding activity, oviposition, F1 progeny, prevent perforation, and weight loss of Katana 1 peanut seeds, and mortality of male and female A. fasciculatus